2006
DOI: 10.1016/j.cardiores.2005.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of matrix metalloproteinases and TIMPs

Abstract: Matrix metalloproteinases (MMPs), also called matrixins, function in the extracellular environment of cells and degrade both matrix and non-matrix proteins. They play central roles in morphogenesis, wound healing, tissue repair and remodelling in response to injury, e.g. after myocardial infarction, and in progression of diseases such as atheroma, arthritis, cancer and chronic tissue ulcers. They are multi-domain proteins and their activities are regulated by tissue inhibitors of metalloproteinases (TIMPs). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
2,484
2
122

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,820 publications
(2,731 citation statements)
references
References 115 publications
28
2,484
2
122
Order By: Relevance
“…Some reports in the literature show that MMP-9 plays an important role in the degradation of the BM as a result of its ability to degrade collagen IV. 16 Nagase et al 30 and Verma and Hansch 31 demonstrated that MMPs are weakly expressed by tissues under physiologic conditions, whereas high expression of these proteins is observed in neoplastic tissues, owing to an imbalance in the activity of MMPs and their inhibitors (TIMPs). In the present study, high percentage and diffuse expression of TIMP-2 was observed in epithelial and mesenchymal cells of DCs, RCs, and KOTs.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports in the literature show that MMP-9 plays an important role in the degradation of the BM as a result of its ability to degrade collagen IV. 16 Nagase et al 30 and Verma and Hansch 31 demonstrated that MMPs are weakly expressed by tissues under physiologic conditions, whereas high expression of these proteins is observed in neoplastic tissues, owing to an imbalance in the activity of MMPs and their inhibitors (TIMPs). In the present study, high percentage and diffuse expression of TIMP-2 was observed in epithelial and mesenchymal cells of DCs, RCs, and KOTs.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs require posttranslational activation, and active enzymes are then controlled by TIMPs (44). In cartilage, procollagenase activation mechanisms represent a key control point and may not be observed even with prolonged inflammatory cytokine stimulation in vitro (45).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the differential sensitivity to collagen-induced apoptosis could be related to the cell capacity to remodel the matrix, we analyzed by reverse transcriptase-PCR the expression profile of five secreted (MMP-1, -2, -8, -9 and -13) and three membrane-type MMPs (MMP-14 or MT1-MMP, known to cleave COL1 (Morrison and Overall, 2006;Nagase et al, 2006;Sabeh et al, 2009a). Most MMPs were expressed at variable levels in the different cell lines (Figure 2a).…”
Section: Mmp-14 Protects Cells Against Col1-induced Apoptosismentioning
confidence: 99%
“…To date, type I collagenolytic activity is confined to a small subset of proteinases belonging to either the cysteine proteinase or matrix metalloproteinase (MMP) families (BirkedalHansen, 1987;Nagase et al, 2006;Sabeh et al, 2009a). MMPs are zinc-dependent endopeptidases that play crucial roles in cancer progression (Noe¨l et al, 2008;Kessenbrock et al, 2010), not only by degrading physical ECM barriers, but also by regulating the processing of an increasing panel of molecular mediators of signaling events (Lopez-Otin and Hunter, 2010;Rodrı´guez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%